The Long Shadow of the Global Financial Crisis : Public Interventions in the Financial Sector - Igan, Deniz (IMF Working Papers; Working Paper ;, 2019)
We track direct public interventions and public holdings in 1,114 financial institutions over the period 2007-17 in 37 countries based on publicly available information. We use aggregate official data to validate this new dataset and estimate the fiscal impact of interventions, including the value of asset holdings remaining in state hands at end-2017. Direct public support to financial institutions amounted to USD 1.6 trillion (USD 3.5 trillion including guarantees), with larger amounts allocated to lower capitalized and less profitable banks. As of end-2017, only a few countries had fully divested the initial support they provided during the crisis. Public holdings were divested faster in better capitalized, more profitable, and more liquid banks, and in countries where the economy recovered faster. In countries where the government stake remained high relative to the initial intervention, private investment and credit growth were slower, financial access, depth, efficiency, and competition were worse, and financial stability improved less.